Correlation between discharge readiness and quality of discharge instructions in Chinese pediatric liver transplant parents - He, Ting; Tang, Li Hua; Huang, Xiaobo; Sa'at, Siti Fatimah (Intisari Sains Medis, 2025)
Introduction: The objective is to examine the present state of preparedness for discharge and the quality of discharge instructions provided to parents of pediatric liver transplant patients and to investigate the relationship between these two factors.